ANALISIS KOMPETENSI, DISIPLIN KERJA DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN STUDI PADA BADAN PENAGGULANGAN BENCANA DAERAH DIY - Yogi saputra; Ignatius Soni Kurniawan (Prodi Magister Manajemen FE-UST, 2021)
This study aims to determine the effect of competence, work discipline and work experience on employee performance on disaster management staff in the Special Region of Yogyakarta. This study uses a saturated sample with a population of 43 respondents. Data collection techniques in this study used a questionnaire with a census. The data analysis method used the classical assumption test, multiple linear test and the coefficient of determination test. The results of this study indicate that the competence variable has a positive and significant effect on employee performance, the work discipline variable has a positive and significant effect on employee performance and the work experience variable has a positive and significant effect on employee performance, simultaneously the variables competence, work discipline and work experience have a positive effect. and significant to employee performance. urgent. significant to employee performance. Keywords: Competence, Work Discipline, Work Experience, Employee Performance.